Transcriptome analysis of childhood Guillain–Barré syndrome associated with supportive care - Hu, Ke; Liu, Wanli; Gan, Yi; Huang, Zhaoxuan (Frontiers in Pediatrics, 2022)
Childhood Guillain-Barré syndrome (GBS) is a rare neurological disease. Early diagnosis followed by precise treatment can reduce mortality. In this study, we collected two transcriptome data between GBS and controls from publicly available database. We identified two distinct down-regulated genes (PTGDS, and AR) in GBS by transcriptome analysis. Based on the two distinct down-regulated genes in GBS group, a two-gene diagnostic signature was developed. Moreover, gene expression analysis for the two-gene was performed on a patient with GBS before and after Supportive Care. RT-PCR results shows that the expression of PTGDS increased after the patient was given supportive care. Therefore, PTGDS might be considered as a potential target for therapeutic target in GBS.